问题 解答题
计算下列各题
(1)
5
6
÷
2
3
-
1
3
×(-9)2+32

(2)(-24)×(
1
12
-
1
6
+
3
8
)

(3)3.14×6.49+3.14×(-5.49)-9×(-3.14)
(4)(-1
1
2
)
2
-(-
2
3
+
1
2
(-
1
6
)
3
答案

(1)

5
6
÷
2
3
-
1
3
×(-9)2+32

=

5
6
×
3
2
-
1
3
×81+9,

=

5
4
-27+9,

=-

67
4

(2)(-24)×(

1
12
-
1
6
+
3
8
),

=

1
12
×(-24)-
1
6
×(-24)+
3
8
×(-24),

=-2+4-9,

=-11+4,

=-7;

(3)3.14×6.49+3.14×(-5.49)-9×(-3.14)

=3.14×(6.49-5.49+9),

=3.14×10,

=31.4;

(4)(-1

1
2
2-(-
2
3
+
1
2
)÷(-
1
6
3

=

9
4
-(-
1
6
)×(-216),

=

9
4
-36,

=-

135
4

填空题
问答题 简答题